2024
DOI: 10.1021/acs.jpclett.4c00008
|View full text |Cite
|
Sign up to set email alerts
|

Host Dependency of Boundary between Strong and Weak Crystal Field Strength of Cr3+ Luminescence

Zhen Song,
P. A. Tanner,
Quanlin Liu

Abstract: Cr 3+ doped near-infrared phosphors hold significant applications and generate considerable research interest. The critical parameter for assessing the strength of the crystal field for Cr 3+ in the Tanabe−Sugano diagram is the boundary value of Dq/B, representing the ratio of crystal field splitting to the Racah parameter B. Nevertheless, there are conflicting values for this parameter, as reported in various studies, such as 2.1, 2.2, and 2.3 for C/B = 4.5−4.8. Moreover, some Cr 3+ doped phosphors with wide-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 47 publications
2
0
0
Order By: Relevance
“…The online calculation program developed by Song et al was used to calculate the D q / B values related to the matrix for the 3d 3 electronic configuration of Cr 3+ . 38 The calculated intersection points for the 2 E and 4 T 2 levels were found to be at 1.94, with the sample's D q / B value at 2.13, close to the intersection point value. The crystal field strength in octahedrally coordinated approximation of Ni 2+ can be calculated using eqn (S1) and (S2) †.…”
Section: Resultssupporting
confidence: 61%
“…The online calculation program developed by Song et al was used to calculate the D q / B values related to the matrix for the 3d 3 electronic configuration of Cr 3+ . 38 The calculated intersection points for the 2 E and 4 T 2 levels were found to be at 1.94, with the sample's D q / B value at 2.13, close to the intersection point value. The crystal field strength in octahedrally coordinated approximation of Ni 2+ can be calculated using eqn (S1) and (S2) †.…”
Section: Resultssupporting
confidence: 61%
“…However, the typical Tanabe–Sugano diagram is designed according to the ideal octahedron and does not apply to all hosts. According to the online calculation program of transition metal 3d 3 electronic configuration energy level developed by Song et al, the D q /B value dependent on the host is calculated, as shown in Figure c. The calculated intersection point of 2 E and 4 T 2 is 2.04, and the D q /B value of the prepared sample is 2.29, which is close to the intersection value.…”
Section: Resultssupporting
confidence: 56%